On the transformative character of collective intentionality and the uniqueness of the human. (3rd April 2017) - Kern, Andrea; Moll, Henrike
Abstract: Current debates on collective intentionality focus on the cognitive capacities, attitudes, and mental states that enable individuals to take part in joint actions. It is typically assumed that collective intentionality is a capacity which is added to other, pre-existing, capacities of an individual and is exercised in cooperative activities like carrying a table or painting a house together. We call this the additive account because it portrays collective intentionality as a capacity that an individual possesses in addition to her capacity for individual intentionality. We offer an alternative view according to which the primary entity to which collective intentionality has to be ascribed is not the human individual, but a "form of life." As a feature of a form of life, collective intentionality is something more than the specific capacity exercised by an individual when she cooperates with others. Collective intentionality transforms all the capacities of the bearers of this specific form of life. We thus call our proposal the transformative account of collective intentionality.